Y-7=2(x-0)

Simple and best practice solution for Y-7=2(x-0) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-7=2(x-0) equation:


Simplifying
Y + -7 = 2(x + 0)

Reorder the terms:
-7 + Y = 2(x + 0)

Reorder the terms:
-7 + Y = 2(0 + x)
Remove the zero:
-7 + Y = 2(x)

Solving
-7 + Y = 2x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + Y = 7 + 2x

Combine like terms: -7 + 7 = 0
0 + Y = 7 + 2x
Y = 7 + 2x

Simplifying
Y = 7 + 2x

See similar equations:

| 1.5x+1=11 | | -12+20h+4h-2h=-10 | | 4(x+5)+5=21-x | | -2x-3y=15x+12 | | 2x-(3-3x)=12 | | (5x+10)(4x-10)= | | x+(12+x)=150 | | -5r-18r-(-16r)=14 | | secx/cosx-tanx/cotx=1 | | (6y-9)=-2y+13(3) | | 3y-14=22-y | | 8x-1=5x-22 | | 19.57=2s+4.61 | | 8v+11-3b=2b+2 | | (13s+7)(6s-18)=0 | | 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 |

Equations solver categories